Improving the Understanding of Pancasila and Citizenship as an Effort to Prevent the Threat of Drugs for Young Generation in Kelurahan Pangkalan Mansyur, Medan Johor - Andriati, Syarifah Lisa; Abduh, Afrita; Lubis, Rafiqoh (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Devotion Team set the title of the service to be "Improving Understanding of Pancasila and Citizenship: The Threat of Drugs for the Young Generation Dispels National Spirit in Pangkalan Mansyur Village" against the background of news of rampant drug crimes that occurred in Pangkalan Mansyur Village and a location that was registered as a problematic location regarding drugs. The socialization aims to develop the love of youth youths for the values ​​contained in Pancasila so as to increase the concept of understanding about citizenship which in turn adds to a sense of love for the homeland. The socialization activity was also enriched by preparing members of the Medan Johor Youth Organization with the provision to become independent individuals who have positive activities by having hydroponic farming skills. The Service Team also facilitates not only hydroponic knowledge, but also equips members of the Medan Johor Youth Organization with hydroponic farming equipment. The hope is that armed with a love for the homeland and knowledge of hydroponic farming equipped with equipment, members of the Medan Johor Youth Organization can start positive activities at home and produce so that they avoid negative activities such as drug dealing.